1993
DOI: 10.1523/jneurosci.13-03-00924.1993
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 1-deficient mutant Drosophila is affected in habituation and associative learning

Abstract: The learning and memory of Drosophila melanogaster strains carrying the Su-var(3)6(01) mutation, which is known to affect the structural gene of a protein phosphatase 1 isoenzyme, PP1(87B), were studied in various behavioral paradigms. Three lines of Drosophila comprising the Su-var(3)6(01) mutation in different genetic backgrounds were shown to have diminished protein phosphatase 1 activity and behavioral anomalies. Associative olfactory learning and visual conditioning were impaired. Olfactory acuity for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 36 publications
0
26
0
4
Order By: Relevance
“…Studies over the last 20 years have established that Drosophila habituate to stimuli in diverse experimental protocols such as the landing response (Rees and Spatz 1989;Asztalos et al 1993), proboscis extension reflex (Duerr and Quinn 1982), cleaning reflex PI ‫ע‬ SEMs are shown for n Ն 7. 0 represents shock avoidance of naive animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies over the last 20 years have established that Drosophila habituate to stimuli in diverse experimental protocols such as the landing response (Rees and Spatz 1989;Asztalos et al 1993), proboscis extension reflex (Duerr and Quinn 1982), cleaning reflex PI ‫ע‬ SEMs are shown for n Ն 7. 0 represents shock avoidance of naive animals.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila, aspects of habituation have been investigated using several diverse assays (Duerr and Quinn 1982;Corfas and Dudai 1989;Asztalos et al 1993;Engel and Wu 1996;Jin et al 1998;Engel et al 2000;Cho et al 2004). With the exception of the proboscis extension reflex (Duerr and Quinn 1982), most assays focused on habituation of peripheral nervous system (PNS) sensory neurons.…”
mentioning
confidence: 99%
“…Associative learning has been induced in many other situations -association between light wavelength and mechanical vibrations [4]; between an odor and the presence of food [5]; between geometrical patterns and heat [6] -, outlining that Drosophila can adapt its behavior based on experience. Several mutants with weak learning and memory capacities have been described (dunce [7]; amnesiac [8]; dopa decarboxylase [9]; rutabaga [liD]; mushroombodies-deranged and mushroom-body-miniature [11]; Shaker [12]; latheo [13]; Su-var(3)6 [14]; DCO [15]; radish [16]; linotte [17] and for a review see [18]). If some mutations alter brain development, other most likely affect brain functioning.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a large number of habituation studies have been reported in Drosophila (Engel and Wu 2009). While habituation research in larger model systems has offered some cellular physiological insight (Fischer and Carew 1993;Bristol and Carew 2005), studies in Drosophila, uniquely possible at a finer level due to the availability of powerful genetic tools and mutant lines, have extended our knowledge to include molecular requirements (Gailey et al 1982;Rees and Spatz 1989;Asztalos et al 1993Asztalos et al , 2007Bouhouche et al 1993;Wu 1996, 1998;Mihalek et al 1997;Engel et al 2000;Megighian et al 2001;Godenschwege et al 2004;Zordan et al 2005;Acevedo et al 2007;Joiner et al 2007;Wolf et al 2007). Molecules identified in these studies have been shown to underlie associative learning as well as habituation, thereby unifying these two different forms of plasticity.…”
mentioning
confidence: 99%